Implementation And Evaluation Of Zerotier-Based Virtual Network For Device Connectivity - Fauzan Prasetyo Eka Putra; Revi Mario Ilhamsyah; Satrio Ananta Efendy; Abdulloh Rizki (Brilliance: Research of Artificial Intelligence, 2025)
The demand for adaptable, secure, and easily deployable network connectivity is increasing rapidly, driven by continuous advancements in information and communication technology. This is particularly evident in the rising adoption of cloud computing, remote work models, and the growing need for scalable and flexible virtual network infrastructures. ZeroTier emerges as an innovative solution that combines the key concepts of Virtual Private Networks (VPN), Software Defined Networking (SDN), and peer-to-peer architectures into a unified platform. This study aims to explore the operational mechanism, implementation procedure, and real-world performance of ZeroTier in enabling seamless connections between devices located across different networks and physical locations. The research methodology includes a comprehensive literature review and practical testing by creating a virtual network using ZeroTier. The evaluation focuses on connection setup, security, ease of configuration, and performance under different network scenarios. The findings reveal that ZeroTier offers a reliable, secure, and efficient virtual networking environment, capable of delivering stable communication with minimal configuration effort. Additionally, it does not require complex infrastructure or technical expertise, making it suitable for academic research, remote work environments, and small to medium-sized businesses. The results suggest that ZeroTier can be considered a viable alternative to traditional VPN solutions and physical network setups, especially in contexts that demand agility, security, and simplicity.